The Role of Parenting Style on Children's Healthy Lifestyle: Authoritative, Authoritarian, and Permissive Parenting Styles - Muhamad Hanif Ramadhan Hanif (Universitas Widya Gama Mahakam Samarinda, 2023)
Abstract Background: In the transitional period after the Covid-19 pandemic, maintaining health is very important, especially for children, because based on the latest findings that the new subvariants of the coronaviruses Omicron BA.4 and BA. 5 are said to be more easily transmitted to groups of children. Parents have an important role in maintaining a child's healthy lifestyle through the parenting style that is applied because parenting style can have implications for a child's healthy lifestyle. Objectives: The purpose of this study was to determine the most significant role of three types of parenting styles on children's healthy lifestyle. Research Metodes: The research method used is a quantitative descriptive research method with a research instrument in the form of a closed questionnaire. The sample used amounted to 60 respondents. Results: The result of this study is that parenting styles of authoritative parents play a significant role in children's healthy living behavior with a contribution of 95.5%. For authoritarian parenting style, it plays a significant role in children's healthy living behavior with a contribution of 77%, and for permissive parenting style, it gives a significant role in children's healthy life behavior with a contribution of 84%. Conclusion: Authoritative parenting styles play a more significant role than authoritarian and permissive parenting styles in children's healthy lifestyles